SNP and Phylogenetic Characterization of Low Viral Load SARS-CoV-2 Specimens by Target Enrichment - Orf, Gregory S.; Forberg, Kenn; Meyer, Todd V.; Mowerman, Illya; Mohaimani, Aurash; Faron, Matthew L.; Jennings, Cheryl; Landay, Alan L.; Goldstein, D. Yitz; Fox, Amy S.; Berg, Michael G.; Cloherty, Gavin A. (Frontiers in Virology, 2021)
Background: Surveillance of SARS-CoV-2 across the globe has enabled detection of new variants and informed the public health response. With highly sensitive methods like qPCR widely adopted for diagnosis, the ability to sequence and characterize specimens with low titers needs to keep pace. Methods: Nucleic acids extracted from nasopharyngeal swabs collected from four sites in the United States in early 2020 were converted to NGS libraries to sequence SARS-CoV-2 genomes using metagenomic and xGen target enrichment approaches. Single nucleotide polymorphism (SNP) analysis and phylogeny were used to determine clade assignments and geographic origins of strains. Results: SARS-CoV-2-specific xGen enrichment enabled full genome coverage for 87 specimens with Ct values <29, corresponding to viral loads of >10,000 cp/ml. For samples with viral loads between 103-106 cp/ml, the median genome coverage for xGen was 99.1%, sequence depth was 605X, and the “on-target” rate was 57 ± 21%, compared to 13%, 2X and 0.001 ± 0.016%, respectively, for metagenomic sequencing alone. Phylogenetic analysis revealed the presence of most clades that existed at the time of the study, though clade GH dominated in the Midwest. Conclusions: Even as vaccines are being widely distributed, a high case load of SARS-CoV-2 infection persists around the world. Viral genetic surveillance has succeeded in warning the public of new variants in circulation and ensured that diagnostic tools remain resilient to a steadily increasing number of mutations. Target capture offers a means of characterizing low viral load samples which would normally pose a challenge for metagenomic sequencing.